Pan-cancer analysis identifies DDX56 as a prognostic biomarker associated with immune infiltration and drug sensitivity - Ruan, Zhaohui; Zhang, Yuetong; Quan, Qi; Jiang, Jiaxin; Wang, Qianyu; Zhang, Yujing; Peng, Roujun (Frontiers in Genetics, 2022)
DDX56, a member of the RNA helicase family, is upregulated in colon adenocarcinoma, lung squamous cell carcinoma, and osteosarcoma. However, the relationships between DDX56 and other tumors are not clear, and the molecular mechanism of its action is not fully understood. Here, we explore the biological functions of DDX56 in 31 solid tumors and clarify that DDX56 can promote oncogenesis and progression in multiple tumor types based on multi-omics data. Bioinformatics analysis revealed that the cancer-promoting effects of DDX56 were achieved by facilitating tumor cell proliferation, inhibiting apoptosis, inducing drug resistance, and influencing immune cell infiltration. Furthermore, we found that copy number alterations and low DNA methylation of DDX56 were likely to be related to aberrantly high DDX56 expression. Our results suggest that DDX56 is a potential pan-cancer biomarker that could be used to predict survival and response to therapy, as well as a potential novel therapeutic target. We validated some of our results and illustrated their reliability using CRISPR Screens data. In conclusion, our results clarify the role of DDX56 in the occurrence and development of multiple cancers and provide insight into the molecular mechanisms involved in the process of pathogenesis, indicating a direction for future research on DDX56 in cancers.